A century of human‐driven changes in the carbon dioxide concentration of lakes. Issue 2 (1st February 2016) - Perga, Marie‐Elodie; Maberly, Stephen C.; Jenny, Jean‐Philippe; Alric, Benjamin; Pignol, Cécile; Naffrechoux, Emmanuel
Abstract: Now that evasion of carbon dioxide (CO2 ) from inland waters is accounted for in global carbon models, it is crucial to quantify how these fluxes have changed in the past and forecast how they may alter in the future in response to local and global change. Here we developed a sediment proxy for the concentration of summer surface dissolved CO2 concentration and used it to reconstruct changes over the past 150 years for three large lakes that have been affected by climate warming, changes in nutrient load, and detrital terrigenous supplies. Initially CO2 neutral to the atmosphere, all three lakes subsequently fluctuated between near equilibrium and supersaturation. Although catchment inputs have supplied CO2 to the lakes, internal processes and reallocation have ultimately regulated decadal changes in lake surface CO2 concentration. Nutrient concentration has been the dominant driver of CO2 variability for a century although the reproducible, nonmonotonic relationship of CO2 to nutrient concentration suggests an interplay between metabolic and chemical processes. Yet for two of these lakes, climatic control of CO2 concentrations has been important over the last 30 years, promoting higher surface CO2 concentrations, likely by decreasing hypolimnetic carbon storage. This new approach offers the unique opportunity to scale, a posteriori, the long‐term impact of human activities on lake CO2 . Key Points: Surface CO2 concentrations of three large lakes are assessed over the last 150 years Nutrient concentration has been the primary, long‐term control of lakes surface CO2 Over the last decades, climate warming can take over nutrient control on lake CO2